Development of a Mini ERP Application Using Agile Methodology for Optimizing Production Processes in a Fabric Manufacturing Company - Febriyani, Widia; Suakanto, Sinung (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The rapid advancement of information technology has dramatically impacted various industries, prompting organizations to adopt computer-based systems that boost innovation and business efficiency. It has become an industry cornerstone, driven competition and enabling companies to enhance production efficiency, creating adaptable business models that align with Goal 9 of the 2030 Sustainable Development Goals (SDGs). This goal promotes strengthening infrastructure, fostering innovation, and supporting sustainable industrial growth, which is crucial for achieving sustainable development and community empowerment. In the textile manufacturing industry and among small to medium-sized enterprises (SMEs), companies often struggle to manage multiple operational areas due to a lack of integration in management systems like order processing, inventory, production, delivery, and finance. This reliance on manual processes can lead to errors, delays, and data inaccuracies, impacting customer satisfaction and competitiveness. To tackle these issues, this study proposes developing a mini-ERP system tailored to small and medium-sized companies, particularly textile manufacturers. This system aims to integrate various business functions into a centralized platform, enhancing operational efficiency, minimizing errors, and improving customer service. However, challenges such as customization, implementation costs, and staff training must be addressed. Using a qualitative approach, this research includes in-depth interviews, observations within textile companies, and document analysis. The waterfall model guides the development process, ensuring thorough task completion at each stage. The goal is to design and implement an ERP system that meets the unique needs of textile manufacturers while ensuring seamless adoption and maximum benefit.